PARTICIPATION AND CITIZENS 'PARTICIPATION IN PROVIDING EFFICIENT ACTIVITIES OF LOCAL SELF-GOVERNMENT BODIES (IN THE CONTEXT OF DECENTRALIZATION REFORM) (Economic journal of Lesya Ukrainka Volyn National University, 2020)
It is noted that in the conditions of democratization of public life and implementation of the decentralization reform in Ukraine, successful development of territorial communities should depend first of all on the participation of the people who live there. It is shown that the growth of civic activity will become organized in nature, provided that the activities of the bodies of self-organization of the population are created and expanded. Forms and mechanisms of citizen participation in ensuring the effective activity of local self-government bodies are grounded, among which local initiatives occupy a special place. An example of their successful implementation in Vinnytsia at the expense of the Public Initiatives Budget, which is part of the budget of the city community, is given. The necessity of participation of citizens in local development, in particular in the development and approval of schemes for planning and development of settlements, the approval of the Strategy for the development of territorial communities, the implementation of infrastructure projects, the formation and distribution of local budget expenditures have been proved. The reasons for the lack of qualified personnel in the local self-government bodies, especially in the rural united territorial communities, were identified. The prospects of ensuring the effective functioning of local self-government bodies in connection with the transition to e-government and the use of e-democracy tools such as e-petitions, public participation budgets, public procurement control system ProZorro, e-declarations and more are revealed. New opportunities are opened for this purpose to control the activity of local self-government bodies by citizens and the state. The necessity of introduction of a special system of state supervision over the activity of local self-government bodies on the basis of the institute of prefects has been proved. It is concluded that new forms of participation of citizens and the state in the activities of local self-government require the use of adequate methods of assessing its effectiveness.
Keywords: local self-government, decentralization reform, united territorial community, participatory democracy, prefect institute, effectiveness of local self-government.